Theory of Mind in Euthymic Bipolar Patients and First-Degree Relatives. Issue 3 (March 2017) - Santos, Josep Manel; Pousa, Esther; Soto, Estel; Comes, Anna; Roura, Pere; Arrufat, Francesc X.; Obiols, Jordi E.
Abstract : Abstract: The present study analyzed the capacity for mentalization of patients with bipolar disorder (BD) and their first-degree relatives (FDR) and examined the implications of clinical variables and cognitive deficits. The study recruited 31 patients with type I BD, 18 FDR, and 31 paired healthy controls. Their capacity for mentalization was explored by means of first- and second-order false-belief tasks, the hinting task, and the Movie for the Assessment of Social Cognition (MASC). Patients and FDR were found to have a theory of mind (ToM) deficit when they were evaluated with the MASC, which was also related to a worse neurocognitive performance and to being a patient or FDR. The evidence of ToM deficits in FDRs supports the hypothesis that these deficits could be an independent trait marker for cognitive deficit. Further research is needed on FDR of patients with BD, using sensitive ToM assessment instruments such as the MASC.